2016
DOI: 10.1021/acs.langmuir.6b00808
|View full text |Cite
|
Sign up to set email alerts
|

Free-Standing, Nanopatterned Janus Membranes of Conducting Polymer–Virus Nanoparticle Arrays

Abstract: Nanostructured mesoscale materials find wide-ranging applications in medicine and energy. Top-down manufacturing schemes are limited by the smallest dimension accessible; therefore, we set out to study a bottom-up approach mimicking biological systems, which self-assemble into systems that orchestrate complex energy conversion functionalities. Inspired by nature, we turned toward protein-based nanoparticle structures formed by plant viruses, specifically the cowpea mosaic virus (CPMV). We report the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Similarly, plant viral particles are being evaluated on various technological platforms that gain enhanced or even novel functionality through an integration of multivalent, selectively addressable bionanostructures (Fan et al, 2013;Culver et al, 2015;Koch et al, 2016;Dragnea, 2017;Narayanan and Han, 2017;Chu et al, 2018a;Chen et al, 2019;Wege and Koch, 2020). Uses as templates for inorganic and synthetic compounds have led to biohybrid materials of convincing properties (Douglas and Young, 1998;Bittner et al, 2013;Vilona et al, 2015;Tiu et al, 2016;Wen and Steinmetz, 2016;Lee et al, 2017;Zhang et al, 2018;Eiben et al, 2019), such as high-capacity battery electrodes or spatially ordered dye ensembles for light-harvesting. If employed as immobilization scaffolds for biomolecules, from peptides and antibodies up to enzymes, plant VLPs exhibit special advantages (Sapsford et al, 2006;Werner et al, 2006;Comellas-Aragones et al, 2007;Minten et al, 2011;Aljabali et al, 2012;Pille et al, 2013;Uhde-Holzem et al, 2016;Roeder et al, 2017;Dickmeis et al, 2018;Koch et al, 2018b;Tian et al, 2018;Yuste-Calvo et al, 2019a;Aves et al, 2020;Park et al, 2020).…”
Section: Applicability Of Plant Viral Nanoscaffoldsmentioning
confidence: 99%
“…Similarly, plant viral particles are being evaluated on various technological platforms that gain enhanced or even novel functionality through an integration of multivalent, selectively addressable bionanostructures (Fan et al, 2013;Culver et al, 2015;Koch et al, 2016;Dragnea, 2017;Narayanan and Han, 2017;Chu et al, 2018a;Chen et al, 2019;Wege and Koch, 2020). Uses as templates for inorganic and synthetic compounds have led to biohybrid materials of convincing properties (Douglas and Young, 1998;Bittner et al, 2013;Vilona et al, 2015;Tiu et al, 2016;Wen and Steinmetz, 2016;Lee et al, 2017;Zhang et al, 2018;Eiben et al, 2019), such as high-capacity battery electrodes or spatially ordered dye ensembles for light-harvesting. If employed as immobilization scaffolds for biomolecules, from peptides and antibodies up to enzymes, plant VLPs exhibit special advantages (Sapsford et al, 2006;Werner et al, 2006;Comellas-Aragones et al, 2007;Minten et al, 2011;Aljabali et al, 2012;Pille et al, 2013;Uhde-Holzem et al, 2016;Roeder et al, 2017;Dickmeis et al, 2018;Koch et al, 2018b;Tian et al, 2018;Yuste-Calvo et al, 2019a;Aves et al, 2020;Park et al, 2020).…”
Section: Applicability Of Plant Viral Nanoscaffoldsmentioning
confidence: 99%
“…Based on these studies, we understand that plant-based PVNs providing multivalent display scaffolds can exhibit nanotopographical features that promote cell adhesion and differentiation. Advincula et al reported the formation of hierarchical CPMV nanoparticle assemblies on colloidal-patterned, conducting polymer arrays [ 49 ] where the electrostatic interaction between the CPMV and the pyrrole-based copolymers drove the site-specific assembly on the nanopatterned conduction polymer array.…”
Section: Pvn Assemblymentioning
confidence: 99%
“…The electrostatic adsorption of CPMV onto carboxylic acid moieties present in an inverse opal-patterned conducting polypyrrole copolymer film can be released from the substrate via an electrochemical trigger thus producing a 2D thin film (Tiu et al, 2016). The close packing of viral particles can serve as a template for the deposition of plasmonic particles to explore metamaterial properties in a 2D plane.…”
Section: D and 3d Materials With Potential Metamaterials Applicationsmentioning
confidence: 99%